The Contribution of the Free Reading to the Formation of Literacy Character and Religious Values of Reading Community Members in Lamongan - Ibriza Mazidah; Retno Nuzilatus Shoimah; Lailatul Maghfiroh (Yayasan Rahmat Islamiyah, 2026)
The low level of reading literacy and character development in Indonesia has become a serious challenge in contemporary Islamic education, particularly in Lamongan City. This study aims to analyze the contribution of free reading activities in shaping literacy character and religious values among members of the moco.bareng reading community at Lamongan Town Square. This research employs a descriptive qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with community members, and field documentation. The results indicate that the moco.bareng community plays a significant role in transforming the character of its members through three main dimensions: cognitive (information analysis skills), professional (public speaking and managerial skills), and religiosity (internalization of spiritual values in literacy activities). Therefore, this community demonstrates that public spaces can effectively function as laboratories for character education that integrate intellectual intelligence with religious values within a non-formal education context.